Development of gross motor skills in children under the age of 3 years: a decision tree approach - Xiong, Yuxiang; Hu, Xuhuai; Cao, Jindan; Shang, Li; Yao, Yibei; Niu, Ben (Frontiers in Public Health, 2024)
The early years of life are critical for gross motor development (GMD). Therefore, based on decision tree modeling, this study examined the influences on gross motor development among children under the age of three and ranked the key factors.Based on randomized stratified sampling, 9,507 children aged 0-3 years in Shenzhen were included in this study. The Ages and Stages Questionnaires (ASQ) was utilized for the assessment of gross motor development.The chi-square test was used to compare groups, and variables were screened using univariable and multivariable regression analyses. Decision tree modeling was emplpyed to rank the importance of statistically significant variables.The research found a prevalence of gross motor developmental delay of 1.41% among the respondents.The accuracy of the decision tree model is 70.96%. The results demonstrated a strong correlation between seven variables affecting the gross motor development of children, which were ranked based on the importance: Age, Whether to provide supplementary food, Average time spent interacting with children, Family type, Feeding method, Mode of delivery, and Birth order.The risk of gross motor developmental delay increases with age. Furthermore, supplementary food and interacting with orther children are critical factors in improving children's GMD delay. It is therefore imperative to enhance the monitoring of children's gross motor skills through regular developmental assessments that detect potential GMD delays. Moreover, family type, feeding method, mode of delivery, and birth order were also predictive factors of GMD delay.